Authentizität: Sprach-, begriffs- und beziehungsgeschichtliche Aspekte - Lobenstein-Reichmann, Anja (Linguistik online, 2020)
This article discusses the historicity of the concept “authenticity”, the etymology of the word authenticity and its use with all the interpersonal consequences in historical discourses as it is illustrated with examples from German literature and the history of the Lutheran Reformation.
Gesehen am 20.04.2023